Pengaruh Pelayanan Prima Terhadap Kepuasan Nasabah - Handini Khaerunnisa (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2013)
This study aimed to determine the effect of excellent service to the satisfaction of the customers of Bank Jabar Banten branch of Pandeglang. Its population is a customer of Bank Jabar Banten branch Pandeglang utilize banking services on a daily basis, which amounts to 200 customers. Then the samples are to be taken as 20% of the daily attendance list of 40 clients. Analysis of the data used in solving this problem is to use quantitative analysis. Judging from the simple correlation coefficient between the variables known to service excellence and customer satisfaction variable has a very strong relationship. Finally it can be proved from the test of the hypothesis that shows that tcount ttable, then Ha received or in other words, there is the influence of excellent service to the customers satisfaction.